Acute Alcohol Effects on Narrative Recall and Contextual Memory: An Examination of Fragmentary Blackouts - Wetherill, Reagan R. (2011)
The present study examined the effects of alcohol consumption on narrative recall and contextual memory among individuals with and without a history of fragmentary blackouts in an attempt to better understand why some individuals experience alcohol-induced memory impairments whereas others do not, even at comparable blood alcohol concentrations (BACs). Standardized beverage (alcohol, no alcohol) administration procedures and neuropsychological assessments measured narrative recall and context memory performance before and after alcohol consumption in individuals with (n = 44) and without (n = 44) a history of fragmentary blackouts. Findings indicate acute alcohol intoxication led to impairments in free recall, but not next-day cued recall. Further, participants showed similar memory performance when sober, but individuals who consumed alcohol and had a positive history of fragmentary blackouts showed greater contextual memory impairments than those who had not previously experienced a fragmentary blackout. Thus, it appears that some individuals may have an inherent vulnerability to alcohol-induced memory impairments due to alcohol’s effects on contextual memory processes.